Upadacitinib for the treatment of radiographic axial spondyloarthritis — case series and review of the literature - Giuseppe Lopalco; Arianna D’Antonio; Maria Sole Chimenti; Florenzo Iannone (Drugs in Context)
Upadacitinib is a Janus kinase (JAK) inhibitor approved for the treatment of different rheumatic diseases, including axial spondyloarthritis (axSpA). In phase III clinical trials, upadacitinib was associated with rapid and significant improvement in disease parameters, including scores for pain, function and mobility, signs of structural damage, and patient-reported outcomes, and had an overall incidence of adverse events similar to that in the placebo group. Improvement in axSpA disease severity was observed in both biologic-naive patients and those with prior biologic exposure, and this improvement was sustained during open-label treatment. Indirect comparisons with other agents suggest that upadacitinib is more effective than biologics and other JAK inhibitors in patients with axSpA and is associated with the lowest number-needed-to-treat. Long-term safety data indicate that upadacitinib is well tolerated in patients with axSpA, with a low rate of infections, malignancies, major adverse cardiovascular events and thromboembolism. Four case studies described here illustrate the effectiveness of upadacitinib in a range of real-world patients with axSpA, including patients with early disease and those who have been pre-treated with biologics.